Aplikasi Manajemen Keuangan Berbasis Web Dinas Komunikasi dan Informatika Kabupaten Tanah Laut - Noor, Agustian; Hadi, Syaiful (Teknik Informatika, Politeknik Negeri Tanah Laut, 2019)
The financial area of Diskominfo has activities such as spending budget activities, DPA activities and printing receipts and financial management processes on the Diskominfo to conduct budget funds for each activity and to conduct data Budget, in the process of disbursement of activities is still difficult to do because in the process of data Input and print data is still done in a conventional way.Employees come to the admin to ask for the creation of financial receipts for DPA activities, the admin makes a receipt that is asked by the employee by inputting data data in the form of DPA activities, DPA programs, recipient name and activity funds.Then admins submit a receipt that has been made to the verifier to verify that the budget data and activity data are correct.If the data has been checked by the Verificator and the data stated is valid then the receipt is left to the treasurer for the process of disbursement of data on DPA activities.These problems can be solved with an application that facilitates the work in the field of finance.The built-in and computerized financial management applications make it easier for the financial part to manage financial data more effectively and efficiently.Construction of this system can help the financial part in making financial receipts to the Communications and Informatics Service of Tanah Laut.